No Efficacy with Noninvasive Brain Stimulation for Painful Legs and Moving Toes : A Case Report - Brück, Anna; Pullinen, Jaakko; Nummelin, Janne; Lehto, Saara; Joutsa, Juho (Karger, 2025)
Introduction: Painful legs and moving toes (PLMT) is a rare neurological disorder characterized by neuropathic pain and involuntary movements in the lower limbs. The pathophysiological mechanisms are unclear, but central mechanisms might be involved, suggesting that noninvasive brain stimulation might be helpful. Thus far, no reports have been published on noninvasive brain stimulation to treat PLMT.
Case Presentation: A 70-year-old female had a 1-year history of PLMT. After several unsuccessful medical attempts, the patient received repetitive transcranial magnetic stimulation and transcranial direct current stimulation to alleviate the pain and involuntary movements with no benefit.
Conclusion: This is the first report on noninvasive brain stimulation in a PLMT patient. Although ineffective in our patient, noninvasive brain stimulation should be further studied in this often difficult to treat and debilitating syndrome.